Conceptual understanding of third grades for axial symmetry - Wallner, Melina; Häsel-Weide, Uta (International Symposium in Elementary Mathematics Teaching. Proceedings: New Directions in Elementary Mathematics Education)

Nachhaltigkeit durch Daten im MBSE: Einblick in die Entwicklung eines Modell-Empfehlungssystems - Tissen, Denis; Tschirner, Christian; Koldewey, Christian; Dumitrescu, Roman (Tag des Systems Engineering)

A process-model for tailoring prototyping of cyber-physical systems - Tissen, Denis; Koldewey, Christian; Dumitrescu, Roman

Hypernetworks: Cluster Synchronization Is a Higher-Order Effect - von der Gracht, Sören; Nijholt, Eddie; Rink, Bob (SIAM Journal on Applied Mathematics)
Many networked systems are governed by non-pairwise interactions between nodes. The resulting higher-order interaction structure can then be encoded by means of a hypernetwork. In this paper we consider dynamical systems on hypernetworks by defining a class of admissible maps for every such hypernetwork. We explain how to classify robust cluster synchronization patterns on hypernetworks by finding balanced partitions, and we generalize the concept of a graph fibration to the hypernetwork context. We also show that robust synchronization patterns are only fully determined by polynomial admissible maps of high order. This means that, unlike in dyadic networks, cluster synchronization on hypernetworks is a higher-order, i.e., nonlinear, effect. We give a formula, in terms of the order of the hypernetwork, for the degree of the polynomial admissible maps that determine robust synchronization patterns. We also demonstrate that this degree is optimal by investigating a class of examples. We conclude by demonstrating how this effect may cause remarkable synchrony breaking bifurcations that occur at high polynomial degree.
Keywords: Applied Mathematics

Private Set Intersection using Third Generation FHE - Anonymous, A.

Rational Models in Cryptography Applied to Matching - Anonymous, A.

Platform Approach for Modularising Battery Electric fast Ferries - Seidenberg, Tobias; Disselkamp, Jan-Philipp; Jürgenhake, Christoph; Anacker, Harald; Dumitrescu, Roman; Papanikolaou, Apostolos (Proceedings of the Design Society)
Abstract The transportation sector is responsible for a relevant share of the total emissions and offers great potentials. It is necessary to implement as many zero-emission mobility systems as possible in the shortest time. For fast ferries, which are a relevant transport manner for a large share of the global population, technical issues could be solved and the successful operation was demonstrated. Up to today high-speed ships have been fully individually designed because physical effects demand for an individual optimisation for each use-case. Specifically for battery electric ships the overall efficiency is crucial to ensure not only an ecological but also economical operation. With today's methods the design and production of such an individual designed ferry does take too long. To cover the rising demand, new approaches for mass production need to be established. In this paper we describe a method for designing a platform for ships with the example of a battery electric fast ferry. The focus is on the actual modularisation, as other aspects like requirements or results of our example case are published elsewhere and are therefore just included briefly. The method is validated on the world's first battery powered high-speed ferry.

A systematic literature review on the Digital Twin of the factory in the context of the product and factory lifecycle - Cieply, Jonas; Disselkamp, Jan-Philipp; Dyck, Florian; Alturk, Waddah; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Development of a modular architecture for complex mechatronic systems - Seidenberg, Tobias; Disselkamp, Jan-Philipp; Jürgenhake, Christoph; Grobbel, Daniel; Dumitrescu, Roman; Papanikolaou, Apostolos (Procedia CIRP)
Keywords: General Medicine

Integrated product and production development - a systematic literature review - Disselkamp, Jan-Philipp; Cieply, Jonas; Dyck, Florian; Grothe, Robin; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Systems Engineering Potentials and Use Cases for the Offer Phase in Special Purpose Machinery - Wilke, Daria; Humpert, Lynn; Mansheim, Johanna; Anacker, Harald; Dumitrescu, Roman (DS 125: Proceedings of the 34th Symposium Design for X (DFX2023))

Venture Client Model: A systematic Literature Review - Haarmann, Lennard; Machon, Fabian; Rabe, Martin; Asmar, Laban; Dumitrescu, Roman (European Conference on Innovation and Entrepreneurship)
Established companies are increasingly opening their innovation systems to stay ahead of the competition. In this context, collaboration with innovative and agile start-ups are gaining continuously more importance. In the past established companies often used common corporate venturing methods such as incubators, accelerators, or corporate venture capital for collaboration. Compared to these methods the venture client model is relatively new and was invented by BMW employees in 2014. Using the venture client model, established companies become early clients of the start-ups even it is still a venture to do so. Together they carry out a pilot project to develop a proof of concept and validate it under real conditions. If successful, they enter a long-term collaboration to integrate the start-up’s solution into products, processes, or business models of the established company. The aim of this paper is to sum up the current literature and set a foundation for future research on this topic. Therefore, we conduct a systematic literature review. As a result, we provide a definition of the venture client model, describe characteristics, present advantages from the perspective of established companies and start-ups. In addition, we summarize the state of research regarding strategy, process, and organizational structure and for the venture client model. In terms of strategy, future research should elaborate defining elements of a strategy as well as ways to integrate the venture client model into the corporate innovation-ecosystem. Focusing on the process additional research is needed on a venture client reference process and its integration into the corporate’s core processes. Referring to the organizational structure a reference architecture for a venture client unit as well as its positioning within the organization (e.g., innovation management or corporate strategy) should be further investigated.

Framework for Dual Transformation: A Systematic Literature Review on the Interplays between Digitalization and Sustainability - Kürpick, Christian; Kühn, Arno; Olszewski, Luca; Dumitrescu, Roman (2023 IEEE Conference on Technologies for Sustainability (SusTech))

A Technology Foresight Maturity Model - Ellermann, Kai; Asmar, Laban; Dumitrescu, Roman (ISPIM Conference Proceedings)

A process mining maturity model: Enabling organizations to assess and improve their process mining activities - Brock, Jonathan; Löhr, Bernd; Brennig, Katharina; Seger, Thilo; Bartelheimer, Christian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (ECIS 2023 Proceedings at AIS Electronic Library (AISeL).)

Evaluation of the Influence of Different Energy Usage Behavior, Component Dimensionings and PV Orientations on the Suitability and Lifetime of a Hybrid, Hydrogen-Based PV Energy System for a Private Household - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 40th European Photovoltaik Solar Energy Conference and Exhibition)

PV Microinverters: Latest Efficiency Rankings, Energy Yield Assessments, Firmware Issues - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 40th European Photovoltaik Solar Energy Conference and Exhibition)

Vorzeichenrichtige tomographische Rekonstruktion von Ultraschallfeldern mit Hilfe der Schlierentechnik - Hetkämper, Tim; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Electrical and Electronic Engineering; Instrumentation

Systematics for an Integrative Modelling of Product and Production System - Schäfer, Louis; Günther, Matthias; Martin, Alex; Lüpfert, Mariella; Mandel, Constantin; Rapp, Simon; Lanza, Gisela; Anacker, Harald; Albers, Albert; Köchling, Daniel (Procedia CIRP)
Keywords: General Medicine

Virtual Assembly for Engineering – A Systematic Literature Review - Dyck, Florian; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine